Sacral nerve stimulation for faecal incontinence and constipation: a European consensus statement. (20th March 2015) - Maeda, Y.; O'Connell, P. R.; Lehur, P.‐A.; Matzel, K. E.; Laurberg, S.; ,
Abstract: Aim: In Europe during the last decade sacral nerve stimulation (SNS) or sacral neuromodulation (SNM) has been used to treat faecal incontinence (FI) and constipation. Despite this, there is little consensus on baseline investigations, patient selection and operative technique. A modified Delphi process was conducted to seek consensus on the current practice of SNS/SNM for FI and constipation. Method: A systematic literature search of SNS for FI and constipation was conducted using PubMed. A set of questions derived from the search and expert opinion were answered on‐line on two occasions by an international panel of specialists from Europe. A 1‐day face‐to‐face meeting of the experts finalized the discussion. Results: Three hundred and ninety‐three articles were identified from the literature search, of which 147 fulfilled the inclusion criteria. Twenty‐two specialists in FI and constipation from Europe participated. Agreement was achieved on 43 (86%) of 50 domains including the set‐up of service, patient selection, baseline investigations, operative technique and programming of the device. The median of agreement was 95% (35–100%). Conclusion: Consensus was achieved on the majority of domains of SNS/SNM for FI and constipation. This should serve as a benchmark for safe and quality practice of SNS/SNM in Europe.